Ritual Kinship, Volume II : Ideological and Structural Integration of the Compadrazgo System in Rural Tlaxcala - Nutini, Hugo G. (Princeton legacy library., 2014)
This sequel to the first volume of Ritual Kinship (Princeton, 1980) completes a comprehensive account of one of the most pervasive and significant of Latin American institutions. Volume II examines the permanent dimensions of the compadrazgo system and its role in the organization of local society.